Política nacional de resíduos sólidos em Sergipe: avaliação da implementação da política dos consórcios intermunicipais de saneamento - Leal, Alesi Costa Lima (2024)
The general objective of the thesis was to evaluate the implementation of the Brazilian National Solid Waste Policy (PNRS) in the state of Sergipe. As a hypothesis, it was assumed that the implementation of the intermunicipal sanitation consortium policy, as the main guideline for the adequacy of solid waste management (SWM) in the state, was not satisfactorily efficient due to difficulties related to the mobilization of actors and the consequent sharing of waste integrated management. It is important to highlight that not all municipalities adopted the consortium proposal and, therefore, do not share the management's solution actions. Among these municipalities is the capital of Sergipe, Aracaju. The specific objectives are: (i) to ethically and historically present the issue of solid waste as a problem of socio-environmental quality; (ii) observe the guidelines of the State Policy for Integrated Solid Waste Management (Pegris) of Sergipe and its resulting management actions; (iii) examine the content of the PNRS and identify its main guidelines applicable to the State of Sergipe; (iv) analyze the GRS in Sergipe based on the policy of intermunicipal sanitation consortia, highlighting the current situation; and (v) evaluate the implementation of the PNRS in the State of Sergipe, identifying the use of opportunities by the actors involved. From scientific practice in the Area of Environmental Sciences, the approach adopted has an interdisciplinary character, in which different methods were used, with emphasis on documentary analysis, field research and the Lee & Colley review package. The investigation shows its relevance as it comprises an unprecedented study of the GRS of Sergipe, presenting aspects that were met and deficient related to what was directed by the PNRS. The research does not address the issue of waste by specifying a type of waste, or in a very specific location, but rather, in an integral way, solid waste in general, and in the state unit. Among the results obtained, it is worth demarcate that: the consortium policy is fundamental for the execution of the PNRS, which fulfills the mission of structuring the sharing of management activities of the consortium municipalities; there is a need to improve coordination between different government bodies (municipality, consortium and state), as well as between the actors involved, in order to provide greater fluidity to solution actions; and recyclable collector cooperatives play a fundamental role in management, especially in enabling selective collection, and greater recognition of their role in the waste production chain is essential, with greater commitment and support through satisfactory publicprivate partnerships.